Communication Patterns of Leaders of The Faculty of Economics In Responding To Uncertainty of Information on University of South Sumatra - Riko Fardiansyah (Publikasi Indonesia, 2023)
The purpose of this study was to understand the communication patterns of leaders at the Faculty of Economics in responding to information uncertainty at the University of South Sumatra, and to find out the driving and inhibiting factors. The phenomenon of the transfer of leadership from one group of actors to another is a big enough problem, that between the Dean and subordinates in terms of organizational structure, there is no one-unit relationship within the organization. Types of qualitative research. The number of informants was 6 people, using a purposive sampling technique. The data collection tool is interview. Data analysis techniques according to iMiles and Huberman. This research uses Weick's organizational communication theory with 3 dimensions namely, Enactment, Selection, and Retention. The results of the study, (1) Enactment, show that communication between leaders and subordinates in informing campus policies is not optimal with the presence of miss communication, the delivery of information is still to certain members (2) Selection, showing the dean is not optimal in providing clarity of information so that the information received is less relevant to the task being performed. (3) Retention, that everyone working at the University of South Sumatra already has their respective duties and structures within the organization. Obstacle factors occur in the Faculty of Management organization such as miscommunication, bad weather causing difficulties to communicate from long distances.